A Systematic Review of Molecular Autopsy Studies in Sudden Infant Death Cases - Heathfield, Laura Jane; Martin, Lorna Jean; Ramesar, Raj (Journal of Pediatric Genetics, 2018)
Sudden unexpected death is an upsetting event, which can remain unexplained even after post-mortem investigation. Internationally, molecular autopsies have shown to resolve up to 44% of unexplained cases; however, it is currently unclear how many of these were infants. This systematic literature review showed that significantly fewer infant cases were resolved (median: 4%) compared with cohorts of 1 to 45 years old (median: 32%). Further, no study involving indigenous African participants has yet been published. Overall, molecular autopsies hold immense value to living family members and is motivation to explore new avenues in infant cohorts.
Keywords: sudden infant death syndrome; negative autopsy; medico-legal investigation